Plant Stress Scenarios Differentially Affect Expression and IgE Reactivity of Grass Group-1 Allergen (β-Expansin) in Maize and Rice Pollen - Juprasong, Yotin; Songnuan, Wisuwat (Frontiers in Allergy, 2022)
Grass pollen is among the most common outdoor aeroallergens eliciting pollen allergies throughout the world. Grass group-1 allergen or β-expansin is recognized as a major pollen allergen, particularly in the grass family Poaceae. Expression of β-expansin has been shown to be dynamic and can be influenced by environmental stresses. This study evaluated the relative expression of β-expansin and IgE-binding ability of crude pollen extract protein of rice and maize under three different stress conditions: flood, salt, and drought. After 1 week of treatments, anthers containing pollen were collected followed by RNA extraction and cDNA synthesis. To evaluate relative expression, qRT-PCR was performed using specific primers for β-expansin and reference genes. Physiological characteristics of treated and untreated maize and rice: plant height; fresh weight of anthers; number of inflorescences, anthers, and pollen grains were also recorded. To assess IgE-binding ability of proteins in rice pollen extracts, soluble crude proteins were extracted and IgE immunoblot and ELISA were performed using serum samples from grass-allergic subjects and healthy control donors. Results showed that plant height, fresh weight of anthers, number of inflorescences, anthers, and pollen grains of both maize and rice decreased significantly under drought stress conditions, but not in other conditions. Expression of β-expansin in pollen of rice showed an apparent increase in all stress treatments relative to control samples. In contrast, a significant decrease of β-expansin expression was detected in maize pollen under all stress-treated conditions. IgE-reactive protein bands from rice pollen extract proteins were 30 kDa, as expected of the grass-group 1 protein. The intensity of IgE-reactive protein bands and the level of IgE to rice pollen proteins showed significant differences among stress conditions. In conclusion, environmental stresses—flood, salt, and drought, can elicit a change of β-expansin expression and IgE reactivity to grass group-1 pollen allergens. Changes in expression level of this gene likely reflected its importance during stress. However, the response is highly dependent on different schemes employed by each plant species.